UTILIZATION OF CANVA APPLICATION AS ICT LEARNING MEDIA AT SD MUHAMMADIYAH BANDUNG - Destiani, Ilma; Hidayati, Dian (Kopertis Region IV Jabar and Banten, 2023)
In this digital transformation’s era, a wide range of applications appears as tools and media in the use of technology, certainly it becomes so important in the realm of education. The chapter of a knowledge of technology must be taught and even introduced when sitting in school. Using qualitative methods, the study aims to provide solutions for the utilization of canva applications as a tactical-learning media in ICT. This study adopted the diffusion theory of innovation approach that examined the diffusion process and the adoption processes that are occurring in society toward the presence of a new innovation. And use qualitative descriptive approaches to interpret the phenomena. The primary data collection process is carried out through interviews. The study described canva's use as a tactile learning media in ICT learning capable of providing ease and excitement in its learning, as well as of improving student creativity and producing graphic design skills with new innovation. Keywords: Untilization, Canva, ICT, Learning media and Elementary school